Enhancing control over organic cathodes through metal coordination for efficient lithium/sodium ion batteries - Yang, Mingqiang (2024)
Organic cathode materials find increasing use in alkali ion batteries for their ease of synthesis, multiple redox functionalities, and high gravimetric capacity. However, the precise control of alkali ion kinetics to concurrently meet the practical demands of high energy density and cycling stability remains a major unresolved challenge. Here, we propose a simple modification method to achieve efficient control over the lithium/sodium ion adsorption and diffusion kinetics by harnessing metal coordination chemistry of highly π-conjugated porphyrins. We introduce various metal ions (Zn2+, Cu2+, Co2+, and Ni2+) to coordinate with tetra(4-pyridyl) porphyrin (H2TPyP) and therefore to electrochemically modify the active sites. Our findings reveal that nitrogen atoms in pyridyl units serve as primary charge storage sites, and the charge storage ability is influenced by the identity of the central metal ion. Zn-TPyP outperforms the other three ones, exhibiting the highest specific capacity of 163 mAh g−1 in lithium-ion batteries and 135 mAh g−1 in sodium-ion batteries at 0.5 C, mainly attributed to the higher formation energy with the ligand which in turn imparts a higher electron density on the pyridyl moieties, affording stronger binding with the lithium/sodium ions. The high mean diffusion coefficients of lithium/sodium ions also validate the high current densities of Zn-TPyP at 10 C.